Arctic multiuniversity: “Polar bank” of Russia’s intellectual capital in the context of modern threats and risks - A. S. Rodionov; S. P. Vishnyakova; Ya. D. Vishnyakov (Вестник университета)
The article is devoted to the problems of transformation of the domestic educational space of the knowledge economy of the digital socio-economic structure considering modern threats and risks. The study purpose is to form and substantiate the author’s system paradigm of network multiuniversitates for training personnel in the interests of sustainable development of the Arctic zone of the Russia and ensuring national security of the country. The authors substantiate the need for an interdisciplinary and practice-oriented transition to a multi-university network organization of universities for the sustainable development of human resources in Russia. The problematic issues that require special attention and urgent resolution in the field of personnel training for the sustainable development of the Arctic region are identified. The conceptual-theoretical and scientific-methodological foundations of the transformation of the domestic educational space in the interests of harmonization of relations between the market and the state, the individual and society are presented. As an object of the field experiment, it is proposed to create an Arctic multiuniversity as a “Polar Bank” of Russia’s intellectual capital. If the proposed field experiment is successful, the accumulated experience can be spread throughout Russia as an example of recreating the science cities of the digital knowledge economy. The authors used general and particular methods of unity research in contrast to natural sciences and humanities. The research methodology is based on the key provisions of risk theory, the theory of eco-oriented innovative development, taking into account the ecological imperative of technological development.